2013
DOI: 10.1371/journal.pone.0071455
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog-Induced Histone Deacetylase Activation Is Required for Cerebellar Granule Precursor Hyperplasia in Medulloblastoma

Abstract: Medulloblastoma, the most common pediatric brain tumor, is thought to arise from deregulated proliferation of cerebellar granule precursor (CGP) cells. Sonic hedgehog (Shh) is the primary mitogen that regulates proliferation of CGP cells during the early stages of postnatal cerebellum development. Aberrant activation of Shh signaling during this time has been associated with hyperplasia of CGP cells and eventually may lead to the development of medulloblastoma. The molecular targets of Shh signaling involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…2). As histone deacetylase inhibitors have been previously implicated in regulating HH activity (2,26), for the remainder of this study, we focus solely on the BET bromodomain inhibitor I-BET151.…”
Section: Resultsmentioning
confidence: 99%
“…2). As histone deacetylase inhibitors have been previously implicated in regulating HH activity (2,26), for the remainder of this study, we focus solely on the BET bromodomain inhibitor I-BET151.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, HDAC6 overexpression has been observed in medulloblastoma before (28), but no link to the Hh system was made. Surprisingly, these authors saw no effect of the HDAC6 inhibitor Tubastatin on granule cell proliferation or allograft growth (28), which might be related to the relatively low concentrations used. In our hands, prominent Hh inhibition required the use of higher concentrations of HDAC6 inhibitors, indicative of the need to fully block HDAC6 to affect the Hh system.…”
Section: Discussionmentioning
confidence: 99%
“…A bovine study showed that the expression of the Hdac1 gene is higher than that of the Hdac2 and Hdac3 genes in two-cell stage embryos (McGraw et al, 2003). There is no study on the effect of SHH or its agonists in an oocyte maturation medium on Hdac family gene expression, although it has been reported that adding Smoothened agonist (SAG), an SHH agonist, to the culture medium of cerebellar granule precursor (CGP) cells derived from medulloblastoma was accompanied by an increase in the expression and function of Hdac1, 2 and 3 genes (Lee et al, 2013). Our results demonstrated that although Hdac1, 2 and 3 genes are homologous, they show alternative patterns of expression in response to different purmorphamine treatments, which indicates a possible difference in their gene activation process and also their next functions.…”
Section: Discussionmentioning
confidence: 99%